Defensive medicine and cesarean sections in Brazil. Issue 1 (8th January 2021) - Rudey, Edson Luciano; Leal, Maria do Carmo; Rego, Guilhermina
Abstract : Abstract: Brazil has a high rate of cesarean sections (CS) that cannot be solely justified by women's clinical conditions; thus, other causes, for example, CS on maternal request and physicians' fear of litigation as possible influencing factors, cannot be overlooked. This study aimed to identify through a survey whether Brazilian gynecologists and obstetricians (GOs) perform defensive CS. In this cross-sectional, descriptive study, a questionnaire was administered. The target population comprised of GOs who were members of premier Brazilian professional associations of gynecology and obstetrics. A total of 403 GOs participated in the survey using an obstetrics questionnaire about litigation and defensive medicine (DM). Statistical analyses were performed on pairs of variables to determine the risk factors of performing CS due to concerns of complications during vaginal delivery and to avoid lawsuits. The mean age of the GOs was 47.7 years who were mostly female (58.3%) and having worked professionally in both public and private sectors (71.7%). Of all participants, 80.6% had been sued or knew an obstetrician who had been sued. The obstetricians who had been sued or who knew a colleague that had been sued exhibited a significantly higher likelihood of performing defensive CS than physicians who had not been sued or did not know physicians who had been sued. The perception of a higher risk of lawsuits against obstetricians influenced the practice of DM and led to a more than six-fold increase in CSs in specialists with this perception compared to specialists who did not believe the presence of an increased risk of litigation in obstetrics existed. The majority of Brazilian GOs perform defensive CS. It is important to consider DM as one of the causes of high CS rates in Brazil and include it in the development of public policies to reduce these CS rates. Abstract : Supplemental Digital Content is available in the text